LIFE CHANCES IN A (UN)SUSTAINABLE WORLD: EDITORIAL (Glocalism: Journal of Culture, Politics and Innovation, 2024)
As has already been well established, we are individuals living in increasingly individualized societies. One may depict the contemporary subject as the human type who wants to be free in order to become an individual. At the foundation of our societies lies no more some kind of Comune, but the Individuo and his freedom to act as a privato. There are no more “laws” for action, but “freedom” of action. The subject of history is no longer the “political animal”, but the “homo oeconomicus”. In the global cities (cosmo-poleis) there are no more “citizens” of the city (polis), but rather “consumers” searching for self-improvement and self-realization, often coping with the delusions of authenticity and autonomy.